The Future of Ecosystem Services in Asia and the Pacific. Issue 3 (28th July 2016) - Kubiszewski, Ida; Anderson, Sharolyn J.; Costanza, Robert; Sutton, Paul C.
Abstract: We estimated the current value of ecosystem services for terrestrial ecosystems in 47 countries in the Asia and the Pacific region. Currently, these provide $US14 trillion/yr. in benefits, most of which are non‐marketed and do not show up in GDP. We also estimated the changes in terrestrial ecosystem services value for scenarios to the year 2050, built around the four Great Transition Initiative archetypes: (1) Market Forces (MF); (2) Fortress World (FW); (3) Policy Reform (PR); and (4) Great Transition (GT). Results show that under the MF and FW scenarios the ecosystem services value in the region continues to decline from $14 trillion/yr in 2011 to $11 and $9 trillion/yr in 2050, respectively. In the PR scenario, the value is maintained around $14 Trillion/yr in 2050 and in the GT scenario it is significantly restored to $17 Trillion/yr. We also show more detailed maps and results for 8 selected countries in the region (Bhutan, China, India, Philippines, Thailand, Cambodia, Laos, Vietnam) and compare our results with a previous national study of Bhutan. Our results indicate that adopting a set of policies like those assumed in the GT scenario would greatly enhance human wellbeing and sustainability in the region.